Composing Ambiguity : the Early Music of Morton Feldman. - Noble, Alistair (Ashgate Pub., 2013)
Alistair Noble reveals key aspects of Morton Feldman's musical language as it developed during a crucial period in the early 1950s. Drawing models from primary sources, he shows that Feldman worked deliberately within a two-dimensional frame, allowing a focus upon the fundamental materials of sounding pitch in time. Through close reading of several important works, Noble shows that there is a remarkable consistency of compositional method, despite the varied experimental notations used by Feldman at this time. Indeed, much of the language developed by Feldman in this period was still in use ev.